Enhanced Stability of Indocyanine Green by Encapsulation in Zein-Phosphatidylcholine Hybrid Nanoparticles for Use in the Phototherapy of Cancer - Eun-Hye Lee; Mi-Kyung Lee; Soo-Jeong Lim (MDPI AG, 2021)
Indocyanine green (ICG) is a clinically approved near-infrared dye that has shown promise as a photosensitizer for the phototherapy of cancer. However, its chemical instability in an aqueous solution has limited its clinical application. Encapsulating ICG in liposomes, phosphatidylcholine nanoparticles (PC-NP), has shown partial effectiveness in stabilizing it. Prompted by our recent finding that the zein-phosphatidylcholine hybrid nanoparticles (Z/PC-NP) provide an advanced drug carrier compared to PC-NP, we herein investigated the potential of Z/PC-NP as an improved ICG formulation. Dynamic light scattering analysis, transmission electron microscopy, and Fourier-transform infrared spectroscopy studies showed that ICG was encapsulated in Z/PC-NP without hampering the high colloidal stability of the Z/PC-NP. During storage, the Z/PC-NP almost completely inhibited the ICG aggregation, whereas the PC-NP did so partially. The Z/PC-NP also more effectively blocked the ICG degradation compared to the PC-NP. The phototoxicity of ICG encapsulated in Z/PC-NP on cancer cells was twofold higher than that in the PC-NP. The ICG encapsulated in Z/PC-NP, but not in PC-NP, maintained its photocytotoxicity after four-day storage. These findings highlight the promising potential of Z/PC-NP as an ICG formulation that provides a higher stabilization effect than PC-NP.